SUN-515 Use of Plasmapheresis for Treatment of Thyroid Storm Resistant to Antithyroidals - Vega, Myrian Noella Vinan (J Endocr Soc, 2020)
Management strategies of thyroid storm include measures to reduce thyroid hormone synthesis, hormone release, conversion from T4 to T3, and inhibition of the peripheral effects of excessive thyroid hormone. Plasmapheresis has been described as a treatment option when traditional therapy is not successful or not feasible. We present a case of an adult patient who presented in thyroid storm in whom plasmapheresis was used successfully as a bridge to thyroidectomy. 51-year-old female with history of hypertension presented with sudden onset shortness of breath, and palpitations. She had an irregular heart rate of 140BPM, respiratory rate of 40, mean arterial blood pressure 65mmHg. Electrocardiogram confirmed atrial fibrillation with rapid ventricular response and the patient was admitted to the intensive care unit. She was started on diltiazem drip and subsequently received amiodarone and electrical cardioversion due to persistent rapid heart rate. She developed respiratory distress and required endotracheal intubation. Initial thyroid profile revealed low TSH and normal FreeT4, but her FT4 increased above normal on day 2, treatment for thyroid storm was initiated with potassium iodine, hydrocortisone and propylthiouracil. She was kept on propranolol 80 mg q/4h, intravenous esmolol 50 mcg/kg/min, diltiazem drip 5 mg/hr, and was started on Digoxin 0.25 mg q/4h. TSI and TPO were undetectable, and thyroid ultrasound revealed a right nodule measuring 5 x 2.2 x 3.7cm. Thyroid storm was attributed to a toxic nodule exacerbated by exposure to excess iodine (contrast for imaging and amiodarone). Propylthiouracil, hydrocortisone and beta blocker were maximized, and cholestyramine was added, but their heart rate remained elevated, blood pressure worsened requiring synchronized cardioversion. Because of persistent hyperthyroid state, refractory to medical treatment, patient was started on plasmapheresis on day 10 of hospitalization, she underwent 5 sessions with significant reduction in Free T3 and Free T4 (Figure 1), and remarkable improvement in her hemodynamic status and resolution of tachycardia. Patient underwent total thyroidectomy on day 16, without complications. Plasmapheresis has been described as a treatment option for refractory thyroid storm, as a bridge therapy prior thyroidectomy. During plasmapheresis, thyroid-binding globulin, thyroid hormones, cytokines and putative antibodies are removed with the plasma; then the colloid replacement provides new binding sites for circulating free thyroid hormone (2). Although albumin binds thyroid hormone less avidly than TBG, it provides a much larger capacity for low-affinity binding that may contribute to lower free thyroid hormone levels, providing a window for thyroidectomy. 1. Muller C et al, Role of Plasma Exchange in the Thyroid Storm, Therapeutic Apheresis and Dialysis15 (6): 522–531